TECHNIQUES OF PROTECTING CROPS FROM INSECT PESTS IN INTEGRATED PEST MANAGEMENT – INTERCROPPING AND TRAP CROPPING - LALA, ARBUD (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Intercropping and trap cropping are two cornerstone practices adopted under cultural control in preventive integrated pest management. The added crop diversity by implementing these techniques in the field level helps in supporting ecological engineering process to suppress pest population in a greener way. The main target of these methods is the deterrence of colonization to control insect pests through intra field diversity. However, complete knowledge about the crop and pest relationship, ecology, ways and effects of habitat manipulation should be known by analyzing the agroecosystem to get an absolute advantage prior of implementation. Thus, ongoing researches on the choice of suitability of proper crops aim in utilizing this integrated knowledge to produce a cost-effective system and lowering the pest population both together to make it a lucrative model qualitatively and quantitatively. To be specific, this paper aims to give a thorough discussion about these two techniques up to the field implementation level and the challenging regions like higher weather dependency, less effectiveness as a sole control technique etc. are also discussed to get an idea about where we need to improve to make these working with higher efficiency.